Infant feeding practices and childhood acute leukemia: Findings from the Childhood Cancer & Leukemia International Consortium. Issue 7 (24th June 2022) - Schraw, Jeremy M.; Bailey, Helen D.; Bonaventure, Audrey; Mora, Ana M.; Roman, Eve; Mueller, Beth A.; Clavel, Jacqueline; Petridou, Eleni T.; Karalexi, Maria; Ntzani, Evangelia; Ezzat, Sameera; Rashed, Wafaa M.; et al.
Abstract: Increasing evidence suggests that breastfeeding may protect from childhood acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). However, most studies have limited their analyses to any breastfeeding, and only a few data have examined exclusive breastfeeding, or other exposures such as formula milk. We performed pooled analyses and individual participant data metaanalyses of data from 16 studies (N = 17 189 controls; N = 10 782 ALL and N = 1690 AML cases) from the Childhood Leukemia International Consortium (CLIC) to characterize the associations of breastfeeding duration with ALL and AML, as well as exclusive breastfeeding duration and age at introduction to formula with ALL. In unconditional multivariable logistic regression analyses of pooled data, we observed decreased odds of ALL among children breastfed 4 to 6 months (0.88, 95% CI 0.81‐0.96) or 7 to 12 months (OR 0.85, 0.79‐0.92). We observed a similar inverse association between breastfeeding ≥4 months and AML (0.82, 95% CI 0.71‐0.95). Odds of ALL were reduced among children exclusively breastfed 4 to 6 months (OR 0.73, 95% CI 0.63‐0.85) or 7 to 12 months (OR 0.70, 95% CI 0.53‐0.92). Random effects metaanalyses produced similar estimates, and findings were unchanged in sensitivity analyses adjusted for race/ethnicity or mode of delivery, restricted to children diagnosed ≥1 year of age or diagnosed with B‐ALL. Our pooled analyses indicate that longer breastfeeding is associated with decreased odds of ALL and AML. Few risk factors for ALL and AML have been described, therefore our findings highlight the need to promote breastfeeding for leukemia prevention. Abstract : What's new? Breastfeeding may protect against childhood acute lymphoblastic and acute myeloid leukemia (ALL/AML), but few studies have examined exclusive breastfeeding or interactions with other early life exposures. In this international pooled analysis, breastfeeding was associated with reduced risk of ALL/AML. Risk of ALL was lowest among exclusively‐breastfed children or breastfed children who also attended day care. The results indicate a dose‐response relationship between breastfeeding and leukemia and highlight the potentially complex joint effects of early life exposures. Few risk factors for ALL and AML have been identified, and the findings support the need to promote breastfeeding for leukemia prevention.